The Bintan MOS development: contribution of ideas to realize Nusantara marine observation network - Dony Apdillah; Indra Jaya; Muhammad Iqbal; Ratih Deswati; Mahesa Glagah; Bili Kusumah; Agung Tri Nugroho; Imam Syafi’i (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2021)
Several marine research have attempted to design a data observation system using Internet of Things (IoT). In the future, this system is predicted to become a necessity for marine researchers as a strategic technology to continuously access data. Therefore, this study provides information on the development and application of observation and data collection systems using IoT. The coastal weather and tidal data were obtained via the automatic coastal weather station and acoustic gauge respectively. Meanwhile, the various research activities commenced in July, 2018. In the first year, an operational observation system was developed, while comprehensive baseline data such as air temperature, humidity, wind speed, and sea surface level were also collected. This collection system is reliable, provides real-time data, and easily accessible with internet connection. Furthermore, the Bintan Marine Observation System (The Bintan MOS) is also suitable for other uses such as; monitoring water quality and marine mammals, as well as disaster mitigation. The adoption of this system by other sectors potentially conditions marine researchers for data exchange, to fully understand the fluctuations in coastal weather of Western and Eastern Indonesia as well as the tropical and sub-tropical marine weather. This study successfully developed the Bintan MOS, capable of providing reliable information both off-line and real-time.Keywords:Marine observation systemCoastal weatherTidalBintan